Transiciones sombrías: Iglesia, Estado y los registros de defunciones en el Perú - Ramos, Gabriela (2012)
This article examines the tensions between the Catholic Church and the state concerning the establishment of the Civil Register in 19th century Peru, and focuses on death and burial registers. The essay questions the widely accepted interpretation that ideological differences between liberals and conservatives explain such tensions, and argues that it is necessary to consider an ample set of circumstances well beyond legislation and ideology to understand them. Furthermore, this article proposes a hypothesis about the relationship between the construction of the state, the governing of the population, and the secularization of death in Peru.